Efektifitas Penggunaan Quizizz Sebagai Alat Evaluasi Pembelajaran Pendidikan Agama Islam - Syakinah Syakinah; Nurul Zahrah Hayati; Rifky Nur Hidayat; M. Hijra Adha; Tuti Nuriyati (Universitas Pakuan, 2026)
EFFECTIVENESS OF USING QUIZIZZ AS AN EVALUATION TOOL FOR ISLAMIC RELIGIOUS EDUCATION LEARNING This study aims to determine the effectiveness of using Quizizz as an evaluation tool for Islamic Religious Education (PAI) learning on student learning outcomes. The background of this study is based on the still dominant use of conventional evaluations that tend to be monotonous so that they are less able to increase student motivation and involvement in the learning process. This study uses a quantitative approach with a quasi-experimental type and a Nonequivalent Control Group Design. The research sample consists of an experimental class using Quizizz and a control class using conventional evaluation. Data collection techniques were carried out through tests, questionnaires, observation, and documentation, while data analysis used normality tests, homogeneity tests, N-Gain tests, and t-tests (independent sample t-tests). The results of the study showed that there was a significant difference between student learning outcomes in the experimental class and the control class. The experimental class using Quizizz achieved a higher increase in learning outcomes than the control class. The results of the N-Gain test showed that the experimental class was in the medium to high category, while the control class was in the low to medium category. In addition, the results of the hypothesis test showed a significance value <0.05, which means there was a significant effect of the use of Quizizz on student learning outcomes. Thus, it can be concluded that the use of Quizizz as an evaluation tool for Islamic Religious Education learning is effective in improving learning outcomes, motivation, and student involvement in the learning process.